Structuring a MOOC Course - Terry, Lucas; Hafizah, Abdul Halim Yun (Centre for Applied Learning UNIMAS, 2021)
Objectives: 1. To design a course structure and instructional design suitable for MOOC. 2. To present the proposed course structure for MOOC 2021 development.